Naming intervention in a case of semantic variant of primary progressive aphasia: A 2 year follow up study - Karpathiou, Nomiki; Kambanaros, Maria; Potamianou, Dimitra; Lyras, Vasileios; Sakka, Paraskevi (My University, 2018)
Background: The semantic variant of Primary Progressive Aphasia (svPPA), a subtype of Frontotemporal dementia, is a neurodegenerative condition which primarily affects language. Evidence suggests that treatment can improve naming in svPPA and slow the progression of anomia. Aim/s: The purpose of the study was to evaluate a naming intervention which relies on independent practice and to monitor maintenance over two years in a case of svPPA. Method: The participant was diagnosed with mild svPPA (MMSE=28/30, CDR=1). Naming performance was established for the Rossion & Pourtois object set. Three lists (experimental I, experimental II and control) were formed from items which were not named by the participant, matched for relevant psycholinguistic variables. Intervention focused on the semantic features of words. Training lasted for two weeks and consisted of therapistled and daily home practice. Independent practice of the first set continued for another 4 weeks and included copying of the list and confrontation naming of picture cards with the written word behind the picture to assist errorless learning. Follow-up assessments were undertaken at 6 months, one year and two years postintervention. Results: Improvement in naming was still evident at the 2 years follow-up assessment (p=0.008). The difference between the first experimental and control list was significant at 2 years post-intervention (U=761, p<0.05). No difference between the second experimental and control list was found beyond 6 months. Conclusion: Results are consistent with previous research, confirming improvement in naming and deterioration after a period with no practice. This case study suggests that daily independent practice may be used as a means of maintaining treatment gains in svPPA.
Keywords: Intervention; svPPA